2010
DOI: 10.1681/asn.2010040438
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Prevents Osmotic Demyelination Syndrome by Inhibiting the Activation of Microglia

Abstract: Rapid correction of chronic hyponatremia can lead to osmotic demyelination syndrome (ODS), a severe demyelination disease. The microglia that accumulate in the demyelinative lesions may play a detrimental role in the pathogenesis of ODS by producing proinflammatory cytokines, suggesting that they may be a target for therapeutic intervention. Here, we investigated whether minocycline, a selective and potent inhibitor of microglial activation, could protect against ODS in rats. We induced hyponatremia by liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 31 publications
2
38
2
Order By: Relevance
“…These results suggest that the deletion of GABA B Rs in POMC neurons leads to hypothalamic inflammation on a HFD. There is evidence to suggest that hypothalamic inflammation is related to the onset of obesity (Gregor and Hotamisligil, 2011), and previous studies showed that hypothalamic inflammation occurred even in WT mice on a HFD (Zhang et al, 2008;Kirchner et al, 2012;Thaler et al, 2012). Together with the findings in the present study, it is suggested that GABA B Rs in POMC neurons are essential to protect the hypothalamus from inflammation on a HFD.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These results suggest that the deletion of GABA B Rs in POMC neurons leads to hypothalamic inflammation on a HFD. There is evidence to suggest that hypothalamic inflammation is related to the onset of obesity (Gregor and Hotamisligil, 2011), and previous studies showed that hypothalamic inflammation occurred even in WT mice on a HFD (Zhang et al, 2008;Kirchner et al, 2012;Thaler et al, 2012). Together with the findings in the present study, it is suggested that GABA B Rs in POMC neurons are essential to protect the hypothalamus from inflammation on a HFD.…”
Section: Discussionsupporting
confidence: 80%
“…Together with the findings in the present study, it is suggested that GABA B Rs in POMC neurons are essential to protect the hypothalamus from inflammation on a HFD. It is also reported that, with a HFD, gliosis in the hypothalamus is increased and that POMC neurons died by autophagy (Thaler et al, 2012). In contrast, our data showed there is no increase in the expression of gliosis markers (Gfap or CD68) or neuronal loss of POMC.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Rats had ad libitum access to standard chow and tap water until the induction of hyponatremia according to previously described methods. [51][52][53] Briefly, osmotic minipumps (Alzet model 2002 or 2004; DURECT Corporation, Cupertino, CA) containing dDAVP (10 mg/ml; Kyowa Hakko Kogyo Co. Ltd., Tokyo, Japan) were implanted subcutaneously into rats under ether anesthesia. For the moderately or severely hyponatremic groups, dDAVP was injected continuously at rates of 0.3 or 0.7 ng/h, respectively.…”
Section: Animal Experimentsmentioning
confidence: 99%